Design and Implementation of a Light Intensity Monitoring System Using an LDR Sensor Based on Arduino - Muhammad Agil Ibrahim; Ansar Rizal; Didi Susilo Budi Utomo (Lembaga Pengembangan Kinerja Dosen, 2026)
This study presents the design and implementation of a light intensity monitoring system based on Arduino using a Light Dependent Resistor (LDR) sensor. The proposed system is capable of measuring light intensity in real-time, displaying the measured values on an I2C-based LCD, and providing an audible alert through a buzzer when the detected light level falls below a predefined threshold. The methodology involves both hardware and software design, followed by system testing through simulation and real-world implementation. The LDR sensor is configured using a voltage divider circuit to convert variations in light intensity into analog voltage signals, which are then processed by the Arduino microcontroller. Experimental results indicate that the system can effectively classify light conditions into three categories: bright, moderate, and dark, with approximate values of 200, 150, and 50, respectively. Furthermore, the system demonstrates reliable performance by activating the buzzer automatically under low-light conditions. Therefore, the proposed system provides a simple, cost-effective, and efficient solution for real-time light intensity monitoring.